Multiple myeloma with esophageal involvement: A rare case. Issue 1 (2nd November 2021) - Tohata, Misako; Yamamoto, Yorimasa; Harada, Hiroshi; Yoshida, Erika; Takano, Yuichi; Gomi, Kuniyo; Nagahama, Masatsugu; Takahashi, Hiroshi
Abstract: A 77‐year‐old man presented with a spinal cord tumor at the cervical 7/thoracic 1 level and pain and weakness in the right hand. Blood tests revealed anemia, renal dysfunction, and hyperproteinemia. Immunoelectrophoresis revealed the M‐protein component of immunoglobulin G gamma globulin. Bone marrow aspirate contained an increased number of atypical plasma cells. He was diagnosed with symptomatic myeloma and treated with radiation therapy, chemotherapy, and extradural tumor resection. Upper gastrointestinal endoscopy, performed because of anemia progression, revealed a 5‐mm submucosal tumor‐like elevated lesion in the upper thoracic esophagus. On white light observation, the lesion appeared whitish with a central redness. Our patient was diagnosed with extramedullary multiple myeloma. Extramedullary lesions are rare in the gastrointestinal tract. To our knowledge, this case is the first of multiple myeloma with esophageal involvement.